High-throughput, real-time monitoring of engineered skeletal muscle function using magnetic sensing. (September 2022) - Smith, Alec ST; Luttrell, Shawn M; Dupont, Jean-Baptiste; Gray, Kevin; Lih, Daniel; Fleming, Jacob W; Cunningham, Nathan J; Jepson, Sofia; Hesson, Jennifer; Mathieu, Julie; Maves, Lisa; Berry, Bonnie J; et al.
Engineered muscle tissues represent powerful tools for examining tissue level contractile properties of skeletal muscle. However, limitations in the throughput associated with standard analysis methods limit their utility for longitudinal study, high throughput drug screens, and disease modeling. Here we present a method for integrating 3D engineered skeletal muscles with a magnetic sensing system to facilitate non-invasive, longitudinal analysis of developing contraction kinetics. Using this platform, we show that engineered skeletal muscle tissues derived from both induced pluripotent stem cell and primary sources undergo improvements in contractile output over time in culture. We demonstrate how magnetic sensing of contractility can be employed for simultaneous assessment of multiple tissues subjected to different doses of known skeletal muscle inotropes as well as the stratification of healthy versus diseased functional profiles in normal and dystrophic muscle cells. Based on these data, this combined culture system and magnet-based contractility platform greatly broadens the potential for 3D engineered skeletal muscle tissues to impact the translation of novel therapies from the lab to the clinic.